Changing asset endowments and smallholder participation in higher value markets: Evidence from certified coffee producers in Nicaragua - Donovan, J.; Poole, N. (Elsevier, 2014)
This paper examines the capacities of smallholders in Nicaragua to exploit new linkages to certified coffee markets following the coffee crisis. Data on livelihood assets were collected from 292 households, which were clustered to test how differences in outcomes (asset building) reflect variations in initial asset endowments. The results suggest that most households built particular elements of their asset base and increased their resilience to future shocks. However, households struggled to make effective use of the gains for intensifying their livelihoods. Of the least-endowed households, few made investments in the scale or productivity of coffee, and most continued to depend heavily on subsistence production and seasonal off-farm income for survival. In conclusion, improved market access alone, even under relatively favorable market conditions and with considerable external support, will have uncertain impacts on rural poverty if the underlying constraints on household assets and investments are not addressed concurrently.